KARAKTERISTIK PENDIDIKAN DALAM TINJAUAN AL-QUR’AN DAN AS-SUNNAH - Muhammad Firdaus; Fitriana Rusyai Ali (Universitas Muhammadiyah Tangerang, 2020)
The flow of globalization is rolling along with the times. Islamic education has the responsibility of equipping people. Through Islamic education, humans can be directed to good morals, and are open to receive good influence from outside, as well as self-development from within with a foundation of faith and piety to Allah SWT, however, if a negative influence cannot be avoided. Then there will be circles of Muslims who understand Islamic teachings imperfectly, both from the methods and values of education in Islam, which in turn they are oriented to the teachings, methods, values of thought that contrary to Islamic teachings. Therefore, a discussion that explains the characteristics of education in the review of the Qur'an and Sunnah is needed. It is to face the problems faced by Muslims in implementing Islamic education. Which it is by the teachings of Islam comprehensively sourced from the Qur'an, As-Sunnah, and the thought of Islamic scholars. This method has been applied for centuries before Western methods and thought, an education that maintains the originality of Islamic teachings